Investigation of the teacher evaluation process with in Iranian medical education system - Z Parsa Yekta; A Nikbakht Nasrabadi (Tehran University of Medical Sciences, 2004)
Introduction: There are different methods of teacher evaluation .The aim of this study was to investigate process of teacher evaluation in selected Iranian Medical of Sciences Universities. Materials and Methods: In this descriptive-analytic study, we investigate the existing documents and performed serial semi-structured interviews with evaluation staff in the universities. The implementation of the whole process of staff evaluation at universities were also observed. The data were analyzed considering both qualitative and quantitative approaches. The descriptive analytic method as well as content analysis was applied for data analysis. Results: Review of the teachers by students was the dominant method for teacher evaluation in the selected universities. This method have some important advantages and disadvantages which are discussed in this article according to the findings. Conclusion: According to the results of this study, it is highly recommended to use a combination of different methods for evaluation of the university teachers as well as decision making purposes.